Respon Pertumbuhan dan Hasil Tanaman Bayam Merah (Amaranthus tricolor L) Varietas Mira Dengan Pemberian Konsentrasi Air Leri Dan Jenis Media Tanam Hidroponik Sistem Floating Raft - Putri Ratno Wardani; Bastaman Syah; Slamet Abadi (Peneliti.net, 2021)
The research aimed was to determine a combination of rice washing water as well as the type of planting media of red spinach (Amaranthus tricolor) using the Floating Raft method, in order to increase the yield of red spinach plants. The research was conducted in a screen house in Kepuh Al-Jariah Village, Karangpawitan District, Regency Karawang, West Java Province, from August to September 2020. The method used was an experimental method with used Randomized Block Design (RDB) single factor, consisting of 10 treatments and 3 replications, andyielding 30 experimental units. The treatments were: A (AB mix and Rockwool); B (AB mix and Cocopeat); C (25% Rice washing water + Rockwool); D (50% Rice washing water + Rockwool); E (75% Rice washing water + Rockwool); F (100% Rice washing water + Rockwool); G (25% rice washing water + Cocopeat); H (50% Rice washing water + Cocopeat); I (75% Rice washing water + Cocopeat); J (100% Rice washing water + Cocopeat).